Implementation Of The Genre Program In Preventing Early Marriage Among Teenagers In Sidoarjo - Hani, Risa Pramestia; Wibawani, Sri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Sidoarjo Regency is the smallest and most populous area in East Java, with 23% of the population being teenagers aged 10-24 years. Sidoarjo Regency has quite a lot of early marriages among teenagers. In 2023, around 201 marriage dispensations will be recorded, most of which are due to marriage by accident. Therefore, the Sidoarjo Regency government continues to strive to reduce the number of early marriages. Through Department of Women's Empowerment, Child Protection and Family Planning, Sidoarjo Regency, prevention of early marriage is carried out with the Generasi Berencana (GenRe) program. This program provides knowledge to change adolescent behavior patterns for the better. This research aims to describe the implementation of the GenRe program in preventing early marriage in Sidoarjo. The research method used in this research is descriptive with a qualitative approach. This research focuses on the implementation of the GenRe program in preventing early marriage among teenagers in Sidoarjo using Merilee S. Grindle's approach which consists of Content of Policy and Context of Implementation. The research results show that the GenRe Program in Sidoarjo has been implemented considering that the marriage dispensation is slowly decreasing. However, its implementation is considered to have not been optimal due to the fairly wide reach and lack of funding and support from several parties to provide outreach. In conclusion, the GenRe Program in Sidoarjo was able to bring about change even though there were obstacles in its implementation.